Análise das relações interorganizacionais entre as transportadoras do Porto Seco Logística e Transporte de Porto Alegre - Tavares, Alexandre de Souza (Pontifícia Universidade Católica do Rio Grande do Sul, 2013)
Made available in DSpace on 2013-08-07T18:40:57Z (GMT). No. of bitstreams: 1 000424146-Texto+Completo-0.pdf: 1069085 bytes, checksum: 6c530a0e07b6fdd92a77553fb4e2e37e (MD5) Previous issue date: 2010 === Organizations have always sought ways to enable them to increase their competitiveness due to the demands of the market. The interorganizational relations have emerged as very effective alternative to help them cope with these demands. Found in several areas of business is the provision of services, industry or commerce, this kind of work has brought positive results. This type of strategy is growing in Rio Grande do Sul and Brasil, that being abroad has become a standard for business upswing. The assessment of how to develop successful business relationship has been a field of study in emergency. In this sense, the objective of this research is to analyse the interorganizational relationships between carriers of Porto Seco Logística and Transporte of Porto Alegre. From the literature review and six interviews with carriers managers of Porto Seco, there were identified 19 attributes that enabled the analysis of interorganizational relationships between carriers of Porto Seco. This work was developed through a single case study – qualitative sploratory research. The main results were: competition was an attribute found fully between the carriers of Porto Seco, factor that hinders the interorganizational relations, however, the information sharing, provision solutions, productivity, administration and management complexity, the formulation and implementation of collective strategies, research and development, competitive advantage and economies of scale, not exist between the carriers of Porto Seco.Since the preparation of the first rule of the Associação of Porto Seco, to more than 20 years, some attributes were found partially, as such: social relations, trust, integration and interaction, organizational learning, developing organization internal and external and innovation, ability to attract new members and partners, reduction of risk, commitment and cultural development. After the searching was found that the relationship is not effective between the carriers of Porto Seco Logistica and Transporte. === As organizações têm buscado permanentemente caminhos que lhes possibilitem aumentar sua competitividade devido às exigências do mercado. As relações interorganizacionais surgiram como alternativa bastante efetiva para auxiliá-las a fazer frente a estas exigências. Encontradas em várias áreas de negócios, seja na prestação de serviços, indústria ou no comércio, esta forma de trabalho tem trazido resultados positivos. Este tipo de estratégia vem crescendo no Rio Grande do Sul e no Brasil, sendo que no exterior já se tornou um padrão para crescimento empresarial. A avaliação de como desenvolver relações empresariais com sucesso tem sido um campo de estudo em emergência. Neste sentido, o objetivo desta pesquisa é analisar as relações interorganizacionais entre transportadoras de Porto Seco Logística e Transporte de Porto Alegre. A partir da pesquisa bibliográfica e de seis entrevistas com gestores de transportadoras do Porto Seco, foram identificados 19 atributos que possibilitaram a análise das relações interorganizacionais entre as transportadoras do Porto Seco. Este trabalho foi desenvolvido através de um estudo de caso Único-Qualitativo- Exploratório. Os principais resultados foram: a concorrência foi um atributo plenamente encontrado entre as transportadoras do Porto Seco, fator que dificulta as relações interoganizacionais; entretanto, o compartilhamento de informações, a provisão de soluções, a produtividade, a administração e complexidade gerencial, a formulação e implementação de estratégias coletivas, pesquisa e desenvolvimento, vantagem competitiva e ganhos de escala, não existem entre as transportadoras do Porto Seco.Desde a elaboração do primeiro estatuto, da Associação do Porto Seco, há mais de vinte anos, foram encontrados parcialmente alguns aributos, como por exemplo, as relações sociais, a confiança, a integração e interação, aprendizagem organizacional, desenvolvimento interno e externo da organização e inovação, capacidade de atrair sócios e novos parceiros, redução de riscos, comprometimento e desenvolvimento cultural. Após a pesquisa ficou constatado que o relacionamento não é efetivo entre as transportadoras do Porto Seco Logística e Transporte de Porto Alegre.